Parameter optimization and experiment of the vacuum seed meter with double holes for direct seeding of rice - Qian, Cheng; Qin, Wei; Jiang, Youcong; Huang, Zishun; Zhang, Minghua; Wang, Zaiman; Yang, Wenwu; Zang, Ying (International Journal of Agricultural and Biological Engineering, 2025)
Direct seeding of rice is a green planting technique because it reduces irrigation water and lowers agricultural production costs. A vacuum seed meter with a double hole for rice was developed to improve the planting accuracy of direct seeding and to meet the tiny seeding rate. The key components of the vacuum seed meter were theoretically analyzed and designed. The optimal parameters of the seed disturbance structure were determined by the Box-Behnken test using the quality of feed index (each group of holes is 1 to 2), miss index, and multiple index as test indices. The results of the Box-Behnken test showed that the optimal parameters were a height of the seed disturbance structure of 1.65 mm, a diameter of the upper arc of 98.87 mm, and a central angle of the upper arc of 11.4°. Based on the optimal seed disturbance structure, the effect of the shaped hole structure parameters on the planting accuracy was investigated, and the optimal hole width and depth were determined to be 4 mm and 2 mm. CFD-DEM numerical simulations showed that the pressure gradient force on the seeds was greater than the drag force, and the pressure gradient force and drag force were positively correlated with the width of the shaped hole. When the rotational speed was 60 r/min and the vacuum pressure was 2.0 kPa, 2.4 kPa, and 2.8 kPa, the miss index of the vacuum seed meter with Wuyou 1179 as the test material was 3.52%, 2.5%, and 2.22%; the quality of feed index was 92.41%, 92.13%, and 87.13%; and the multiple index was 4.07%, 5.37%, and 10.65%. For Huanghuazhan and Taixiang 812 rice seeds, the planting accuracy of the vacuum seed meter with the double hole can meet the requirements for direct seeding of rice. This study provides a theoretical basis and design reference for rice precision planting technology. Key words: rice; direct seeding; seed meter; planting accuracy; shaped hole; seed disturbance structure; CFD-DEM DOI: 10.25165/j.ijabe.20251802.9335 Citation: Qian C, Qin W, Jiang Y C, Huang Z S, Zhang M H, Wang Z M, et al. Parameter optimization and experiment of the vacuum seed meter with double holes for direct seeding of rice. Int J Agric & Biol Eng, 2025; 18(2): 89–99.